147k views
0 votes
2/3 +y-1/9=7/9 solve for y

1 Answer

4 votes

Answer and Step-by-step explanation:

According to the question the answer you should be getting is :
y =(2)/(9)

Let's solve your equation step by step like this :

Step 1 : Simplify both sides of the equation :


(2)/(y)+-(1)/(9)  =(7)/(9)


(2)/(3)+y+(-1)/(9)=(7)/(9)


(y)+((2)/(3)+(-1)/(9))=(7)/(9) (Combine the like terms)


y+(5)/(9)=(7)/(9)

Step 2 : Subtract 5/9 from both sides :


y+(5)/(9)-(5)/(9)=(7)/(9)-(5)/(9)


y=(5)/(9)

User Holly
by
5.7k points